Trajectory Tracking of a Quadcopter UAV using PID Controller (ELEKTRIKA- Journal of Electrical Engineering, 2023)
UAVs or Drones are aircraft with no onboard pilot to control the flight. They are introduced in a few categories such as single-rotor, multi-rotors, fixed-wing, and hybrid VTOL. As for multirotor drones, quadcopters are the most well-known either commercially or in the research field. Due to its advantages, a quadcopter has been chosen to perform various tasks across various fields such as entertainment, military, meteorological reconnaissance, civil and emergency responses. As the demand for quadcopters has diverged, the required features of quadcopters have also diverged. One of the current features required by quadcopters is the ability to track trajectories. However, due to its nature of non-linearity, under-actuated and unstable, controlling quadcopter for an accurate and stable performance is quite a challenge. Despite the various proposed methods throughout the past decades, PID controller is still used as either the main controller or the base controller in most cases of industrial control, including quadcopter, mainly due to its simplicity and robustness. However, to design a proper PID controller for quadcopter system is a challenge as it defies the control inputs of four with its six degree-of-freedom form, in which six inputs are required to be controlled to ensure a stable and accurate flight. This paper derived a mathematically model of a quadcopter with Newton-Euler’s equation. Some assumptions on the body and structure of the quadcopter are taken into account to make the modelling possible. Then, a manually tuned PID controller is designed to achieve the objective of controlling the operation and stability of the quadcopter during its flight. The designed controller is tested with five different trajectories which are circular, square, lemniscate, zigzag, and spiral. The results show the proposed controller successfully tracks the desired trajectories, which prove PID controller can be used to control a quadcopter.